1981
DOI: 10.1159/000123149
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Channels Involved in the LHRH and SRIF Release from Rat Mediobasal Hypothalamus

Abstract: A superfusion system was used in order to investigate the ionic requirements of luteinizing hormone releasing hormone (LHRH) and somatostatin (SRIF) release from mediobasal hypothalamic (MBH) slices of male adult rats. Slices were superfused with Hepes-buffered Locke medium at 37 °C in an atmosphere of Ch 95%–CO2 5% for 1 h. Bacitracin (2 × 10–5M) was added to the medium to prevent enzymatic degradation of neuropeptides. Depolarizing agents such as potassium (K+) or veratridine stimulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
45
0

Year Published

1983
1983
1998
1998

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(51 citation statements)
references
References 17 publications
6
45
0
Order By: Relevance
“…As already shown for GnRH [10, 12, 15, 31]and GAP [15], repeated stimulation did not significantly deplete tissue stores of HypGnRH. Repeated challenges with several secretagogues did not alter the molecular composition of the released material.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…As already shown for GnRH [10, 12, 15, 31]and GAP [15], repeated stimulation did not significantly deplete tissue stores of HypGnRH. Repeated challenges with several secretagogues did not alter the molecular composition of the released material.…”
Section: Discussionsupporting
confidence: 74%
“…In order to propose a neurohormonal role for HypGnRH, it was necessary to establish whether endogenous HypGnRH, as GnRH itself, is secreted by the Ht in a calcium-dependent manner [10, 11, 12, 13]. It was of further interest to compare its regulation with that of GnRH release.…”
Section: Introductionmentioning
confidence: 99%
“…Noradrenaline depolarized the membrane potential, and increased [Ca2+]i, and then increased GnRH release. Our results are partially consistent with those of a study of mediobasal hypothalamic slices by Drouva et al [12], who reported that depolarizing agents such as potassium or veratridine stimulated GnRH release in a dosedependent manner and that removal of Ca2+ from the medium and administration of voltage-sensitive Ca2+ channel blockers (D-600, Mn2+) blocked potassiumand veratridine-induced release of GnRH. In our study, NA-induced [Ca2+]i increases in GT1-7 cells were also inhibited by the absence of extracellular calcium.…”
Section: Discussionsupporting
confidence: 93%
“…First, activation of VSCCs by high K+-induced depolarization (15) in cultured hypothalamic neurons and GT1-1 neuronal cells leads to increased GnRH release, as in perifused hypothalamic explants (32,33 …”
Section: Discussionmentioning
confidence: 99%